Silogism Analysis of Indonesian Language Education's Students Teacher Training and Science Education Faculty (FKIP) of University of Muhammadiyah Sumatera Utara (UMSU) (Psycholinguistic Studies) - Tepu Sitepu (Budapest International Research and Critics University, 2018)
This study aims to describe the ability of syllogism, both categorical syllogism, syllogism of hypotheses, alternative syllogisms and the entimem of Indonesian Language Education students in the Teacher Training and Education Faculty of North Sumatra Muhammadiyah academic year 2017-2018. The research method used is descriptive exploratory method or Description Exploration Development Research (DEDR). The population of this study amounted to 311 students with details of 160 5th semester students and 151 7th semester students. This research sample consisted of 74 students with details of 40 5th semester students and 34 semester 7 students. The results of the study were through pretest or before applying the cooperative learning model obtained mean = 60 for semester 5 students and mean = 59.53 for semester 7 students. The results of the study through posttest or after the cooperative learning model was applied, mean = 83.70 for semester 5 students and mean = 8 8.70 for 7th semester students. Thus, it can be concluded that the 5th semester of Indonesian Language Education is less capable in syllogism or does not reach the standard of success because the mean is <85, while 7th semester students of Indonesian Language Education are capable in syllogism because it reaches the mean> 85. the two meanings are combined or 74 students become samples, then reach a mean of 83.70 + 88.70 = 86.20> 85 with a success rate of> 85 as many as 48 students of Indonesian Language Education Teacher Training and Education Sciences University of Muhammadiyah North Sumatra (64.86%) 2017-2018 academic year.